2018
DOI: 10.17802/2306-1278-2018-7-2-25-36
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Vascular Tissue Remodeling Using Biodegradable Tubular Scaffolds With Incorporated Growth Factors and Chemoattractant Molecules

Abstract: 25омплексные проблемы сердечно-сосудистых заболеваний К Highlights • The study demonstrates the benefits of using functionalized small-diameter biodegradable vascular graft for de novo vascular tissue formation.• The release of growth factors and chemoattractant molecules into the vascular bed after the graft implantation stimulates neotissue formation and levels out inflammation and calcification. BackgroundCurrently, the search for the bioactive molecules capable of promoting formation of the vascular tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
11
1
7
Order By: Relevance
“…Interestingly, the rates of PHBV/PCL graft resorption in sheep exceed those reported in the literature, that is 3-4 years for PCL and at least 5 months for PHBV [16,17]. In our previous studies, the degradation of PHBV/PCL grafts implanted into rats was also much longer as compared to this experiment [14,15]. In this study, PHBV/PCL-GFmix Hep/Ilo grafts completely degraded only 6 months postoperation.…”
Section: Resultscontrasting
confidence: 47%
See 2 more Smart Citations
“…Interestingly, the rates of PHBV/PCL graft resorption in sheep exceed those reported in the literature, that is 3-4 years for PCL and at least 5 months for PHBV [16,17]. In our previous studies, the degradation of PHBV/PCL grafts implanted into rats was also much longer as compared to this experiment [14,15]. In this study, PHBV/PCL-GFmix Hep/Ilo grafts completely degraded only 6 months postoperation.…”
Section: Resultscontrasting
confidence: 47%
“…Using a rat model of abdominal aorta implantation, we showed that immobilization of angiogenic factors on graft luminal surface led to a rapid repopulation of PHBV/PCL grafts by endothelial progenitor cells [14,15]. Three months following implantation in rats, we observed a complete re-endothelialization along with formation of neointima and the presence of smooth muscle cells producing collagen types I and IV [14,15]. The primary patency of such grafts was 93.3% 12 months following implantation.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…биодеградируемых полимеров [2,3]. При этом дополнительное инкорпорирование в состав полимерных сосудистых матриксов (графтов) биологически активных веществ (ростовых факторов и хемоаттрактантов) стимулирует привлечение и дифференцировку эндогенных прогениторных клеток in situ [4,5].…”
Section: Resultsunclassified
“…Доказано, что молекулы bFGF, SDF-1α поддержали устойчивое VEGF-индуцированное образование качественной эндотелиальной выстилки на внутренней поверхности сосудистого протеза. Высокая первичная проходимость в период 12-месячной имплантации крысам обеспечила формирование сосудистых тканей на месте биодеградируемого матрикса с одновременным снижением интенсивности кальцификации и отсутствием признаков иммунного отторжения [73].…”
Section: основные биологически активные вещества используемые для моunclassified